Are convalescent plasma stocks collected during former COVID‐19 waves still effective against current SARS‐CoV‐2 variants?. Issue 5 (12th January 2022) - Focosi, Daniele; Franchini, Massimo; Joyner, Michael J.; Casadevall, Arturo
Abstract: COVID‐19 convalescent plasma (CCP) was among the few frontline therapies used to treat COVID‐19. After large randomized controlled trials (RCTs) relying on late use in hospitalized patients and/or low antibody titres failed to meet their predefined primary endpoint, the infectious disease community reduced usage of CCP in favour of monoclonal antibodies. Consequently, there are CCP stocks at most transfusion centres worldwide, although scattered usage continues. Further, better designed RCTs are also being launched. The urgent question here is: should we use CCP units collected months before given the largely changed viral variant landscape? We review here in vitro evidence that discourages usage of such CCP units against Delta and other variants of concern. CCP collections should be continued in order to update the armamentarium of therapeutics against vaccine breakthrough infections or in unvaccinated patients and is especially relevant in next‐generation RCTs.